Bifid tongue: Differential diagnosis and a case report. Issue 5 (September 2015) - Siddiqua, Aaisha; Abubaker, Parvez; Saraswati, F.K.; Thakur, Nitin
Abstract: Bifid tongue is a rare congenital anomaly usually associated with syndromes and infrequently associated with nonsyndromic cases. The syndrome most commonly seen with associated finding of bifid tongue is the oro-facial-digital syndrome. Various other syndromes and nonsyndromic cases also have been found to have an associated finding of bifid tongue as an irregular feature. With this article, an attempt is made to evaluate a case of bifid tongue for its association with any of the syndromes reported with bifid tongue and the association of bifid tongue with nonsyndromic cases.